1998
DOI: 10.1086/514686
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Staphylococcus aureus Bacteremia According to Compliance with Recommendations of Infectious Diseases Specialists: Experience with 244 Patients

Abstract: To determine whether recommendations of infectious diseases specialists affect outcome for patients, we evaluated 244 hospitalized patients with Staphylococcus aureus bacteremia. We offered our management recommendations to each patient's physicians and then assessed the clinical outcome for both patients for whom our consultative advice was followed and those for whom our advice was not heeded. All patients were followed up for 12 weeks after their first positive blood culture. Our management advice was follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
240
1
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(270 citation statements)
references
References 25 publications
15
240
1
8
Order By: Relevance
“…12 Health maintenance organizations that restrict access to specialists are associated with a decrease in patients' trust and confidence in their primary care physician, lower patient satisfaction, increased desire to leave the managed care plan, and a lower likelihood of recommending the group to a friend. 13,14 Several studies have shown that specialists do a better job than generalists in the management of patients with suspected myocardial chest pain, 15 unstable angina, 16 acute myocardial infarction, 17,18 asthma, 19,20 diabetes, 21 Staphylococcus aureus bacteremia, 22 and osteoarthritis. 23 In contrast, other studies have shown that specialists were no better than generalists were in the management of patients with severe chronic obstructive pulmonary disease 24 or hypertension and non-insulin-dependent diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…12 Health maintenance organizations that restrict access to specialists are associated with a decrease in patients' trust and confidence in their primary care physician, lower patient satisfaction, increased desire to leave the managed care plan, and a lower likelihood of recommending the group to a friend. 13,14 Several studies have shown that specialists do a better job than generalists in the management of patients with suspected myocardial chest pain, 15 unstable angina, 16 acute myocardial infarction, 17,18 asthma, 19,20 diabetes, 21 Staphylococcus aureus bacteremia, 22 and osteoarthritis. 23 In contrast, other studies have shown that specialists were no better than generalists were in the management of patients with severe chronic obstructive pulmonary disease 24 or hypertension and non-insulin-dependent diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier identification of patients with CRE infection should also lead to earlier consultation with Infectious Diseases (ID) specialists. ID consultation has been associated with favorable outcomes for patients with S. aureus bloodstream infections 50,51 and should similarly benefit patients with invasive CRE infections.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%
“…Spinal infection is a relatively rare condition and accounts for [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].7% of all cases of osteomyelitis [6,11,14,19]. In developed countries, improved public hygiene reduced the incidence of spinal infections in the 1970s; however, several papers [2,3,7,19] have warned that spinal infections have been more frequent recently with the increase of immunocompromised hosts, human immunodeficiency virus (HIV) infection and immigrants from developing countries.…”
Section: Introductionmentioning
confidence: 99%